Isoniazid improves cognitive performance, clears Aβ plaques, and protects dendritic synapses in APP/PS1 transgenic mice - Chen, Jiacheng; Guo, Ning; Ruan, Yuting; Mai, Yingren; Liao, Wang; Feng, Yanqing (Frontiers in Aging Neuroscience, 2023)
Background and objective Alzheimer’s disease (AD) is characterized by amyloid β (Aβ) aggregation and neuroinflammation. This study aimed to investigate the therapeutic effect of isoniazid (INH) against AD. Methods The APP/PS1 transgenic mouse model of AD was adopted. The APP/PS1 mice received oral INH (45 mg/kg/d) for 14 days. The cognitive capability was assessed by the Morris Water Maze test. Amyloid plaques and Aβ levels were determined by immunohistochemistry and ELISA assay. The dendritic spines were analyzed by DiOlistic labeling. Immunofluorescence staining was used to observe the microglia and astrocytes. Results The Morris Water Maze test suggested that INH administration can effectively attenuate the reference memory deficit and improve the working memory of the APP/PS1 mice compared to the untreated mice (all p < 0.001). INH significantly decreased the Aβ plaques in the hippocampus and cortex and reduced the levels of Aβ1-40 and Aβ1-42 in the brain homogenates, cerebrospinal fluid, and serum (all p < 0.001). INH also inhibited enzyme activities of β-site amyloid precursor protein cleaving enzyme 1 (BACE1, p < 0.05) and monoamine oxidase B (Mao-b, p < 0.01). INH significantly increased the protrusion density in the hippocampus (p < 0.01). Immunofluorescence staining revealed that INH significantly reduced the number of activated microglia and astrocytes around the Aβ plaques (both p < 0.01). Conclusion Isoniazid administration effectively improved cognitive performance, cleared Aβ plaques, protected dendritic synapses, and reduced innate immune cells around the Aβ plaques, suggesting that INH could be a potential drug for AD treatment.